Cunha, Jorge, La ética de Jesús. Ediciones Sígueme, Salamanca 2018. - Francisco Martínez Fresneda (Carthaginensia, 2019)
Es recensión de: Cunha, Jorge, La ética de Jesús. Ediciones Sígueme, Salamanca 2018-